PENGALAMAN CAREGIVER KELUARGA DALAM MERAWAT PASIEN KANKER PAYUDARA - Kadek Ana Dwijayanti (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2015)
Breast cancer is the disease that was the first largest case of cancer in Indonesian woman. Breast cancer make a very complex impact for patient and their family. Family caregiver’s has a duty to care for patient, especially in the case of breast cancer. This study is a qualitative study with phenomenological approach that aims to explore family caregiver’s experience in caring for breast cancer patient. In this study, participants were selected by purposive sampling method. There are six participants join in this study. The data were collected using in depth interview technique. The data were analyzed by using Collaizi’s technique. This study indentified 7 themes, that are: 1) lack of knowledge about breast cancer, 2) caregiver’s reactions, 3) caregiver’s task, 4) changes in responsibilities, 5) changes in economic function of the family, 6) complaints against the health care, and 7) caregiver’s expectation. The result show that family caregiver’s can adapt to changes that occur in the family. Family caregiver’s were able to perform their tasks in caring the patient by providing support to the patient for fulfill biological, psychosocial, spiritual, and financial needs